THE INFLUENCE OF LOGICAL MATHEMATICAL INTELLIGENCE, LEARNING INDEPENDENCE AND LEARNING MOTIVATION ON MATHEMATICS LEARNING OUTCOMES OF GRADE XI STUDENTS OF SMA NEGERI 1 MERAUKE - Fredek Batsira; Bettisari Napitulu; Irfan Wahyudi (Penelitian dan Pengembangan Ilmu, 2025)
Intelligence, learning independence and learning motivation on students' mathematics learning outcomes. The type of research used is ex post facto research. The population in this study were all students of grade XI of SMA Negeri 1 Merauke in the 2024/2025 academic year with a total of 398 students. The research sample to be used was 199. Data collection techniques used in this study were questionnaires, tests and documentation. Data analysis techniques in this study include descriptive and inferential data analysis. The results of this study indicate that there is an insignificant effect between mathematical-logical intelligence, learning independence and learning motivation on the mathematics learning outcomes of grade XI students of SMA Negeri 1 Merauke. This is because the results of the f-test obtained Fcount (5.433)> Ftable 3.89 and a significance value (0.001) <0.05.